Gaucher's disease in the lipidomics era. (August 2012) - Fuller, Maria
Human diseases that result directly from alterations in sphingolipid metabolism are generally disorders of the degradation of these compounds. A defect in the lysosomal degradation of glucosylceramide results in the phenotype of Gaucher's disease, the most common of the sphingolipidoses. The majority of cases of Gaucher's disease result from mutations in the gene encoding the lysosomal enzyme, acid β-glucosidase. Although generally regarded as a single-gene disorder, in reality the disorder is complex, multifactorial and progressive. Understanding the pathogenic cascade in Gaucher's disease will require an integrated and convincing biological approach; this review aims to explore how the study of sphingolipids, in addition to glucosylceramide, phospholipids and other related lipids, are advancing us towards achieving this goal.